Designing isolation guidelines for COVID-19 patients with rapid antigen tests - Yong Dam Jeong; Keisuke Ejima; Kwang Su Kim; Woo Joohyeon; Shoya Iwanami; Yasuhisa Fujita; Il Hyo Jung; Kazuyuki Aihara; Kenji Shibuya; Shingo Iwami; Ana I. Bento; Marco Ajelli (Nature Communications, 2022)
Utilizing viral test results to determine isolation length would minimize both the risk of prematurely ending isolation of infectious patients and the unnecessary individual burden of redundant isolation of noninfectious patients. Here, the authors develop a framework to compute the population-level risk of different isolation guidelines with rapid antigen tests.